Coronary CT angiography as an ‘one-stop shop’ to detect the high-risk plaque and the vulnerable patient - Antoniades, C; West, HW (Oxford University Press, 2021)
This editorial refers to ‘Fractional flow reserve derived from computed tomography coronary angiography in the assessment and management of stable chest pain: the FORECAST randomized trial’, by N. Curzen et al., doi:10.1093/eurheartj/ehab444.